A escrevivência de docentes: um processo de reflexão sobre a elaboração de currículo - Cintra, Patrícia (2023)
The present research aims to investigate how teachers involved in the writing of a curriculum during the preparation of didactic material position themselves as authorial subjects, doing so from the intersection of their studies and, mainly, their personal and professional experiences. The curriculum is a space of struggles and power. (APPLE, 1982). Understanding the context of forces and interests that gravitate around it is essential for understanding the choices that are present and the answers it provides: for what and for whom the curriculum is designed. In this sense, we sought to answer how a collaborative curriculum was proposed, focusing on the development of subjects sensitive to social inequalities, which discussed historical and decolonial connections, welcomed multiple perspectives, including diverse and singular voices (such as indigenous and black voices), seeking to open new possibilities (WALSH, 2020). The data was obtained throughout the writing of the chapter analyzed, in which teachers describe and reflect on the writing of the didactic material for students of the initial years of elementary school in a private school in the city of São Paulo, Brazil. The theoretical rationale was based on the understanding of ethical-political suffering (SAWAIA, 1999) in the professional sphere. We sought to understand the role of conatus (ESPINOSA, 1983), and the concept of collaborative writing (EVARISTO, 1996) that seeks an unencapsulated curriculum (LIBERALI, 2019) with the potential for resistance and opening up ways to build a more equitable society. The method of critical collaborative research was used seeking to promote a deliberate transformation of contexts and people involved (LIBERALI; MAGALHÃES, 2004). The research aims to show through the content analysis, the exercise of observing by challenging one's own certainties observation, showing how these writers of their experience can understand each other as researchers. (P. FREIRE, 1996). We understand how the process of collaborative writing points to the feasibility of content inclusion of sensitive subjects in the curriculum, in search of the transformation of society, from the action engaged of these teachers